Responder Analysis of the Effects of Denosumab on Bone Mineral Density in Men Receiving Androgen Deprivation Therapy for Prostate Cancer - Egerdie, Blair (2012)
BACKGROUND: Men with prostate cancer are at risk of experiencing accelerated bone loss and fractures as a result of androgen deprivation therapy (ADT). OBJECTIVE: We evaluated the effects of denosumab, a fully human monoclonal antibody against RANKL, on preservation of BMD at 3 key skeletal sites (lumbar spine [LS], femoral neck [FN], and total hip [TH]) and the distal radius at 36 months both by responder category and individual responses in a waterfall plot analysis. DESIGN, SETTING, AND PARTICIPANTS: This phase 3, randomized, double-blind study of men with non-metastatic prostate cancer receiving ADT investigated the effects of denosumab on bone mineral density (BMD) and fractures. Patients were treated for 36 months. INTERVENTION: Subcutaneous denosumab 60 mg (n=734) or placebo (n=734) every 6 months for up to 36 months. Patients were instructed to take supplemental Calcium and vitamin D. MEASUREMENTS: Primary outcome measure: The percentage change from baseline to month 36 in LS, FN, and TH BMD was measured by dual energy x-ray absorptiometry. BMD at the distal 1/3 radius at 36 months was measured in a sub-study of 309 patients. RESULTS AND LIMITATIONS: At 36 months, significantly more patients in the denosumab arm had increases of >3% BMD from baseline at each site studied compared with placebo (LS, 78% vs 17%; TH, 48% vs 6%; FN, 48% vs 13%; distal 1/3 radius, 40% vs 7%). The percentage of denosumab patients with bone loss at all 3 key BMD sites at month 36 was 1%, as opposed to 42% in placebo arm. At 36 months 69% of denosumab-treated patients had BMD increases at all three sites (LS, TH or FN) compared with 8% of placebo-treated patients. Lower baseline BMD was associated with higher magnitude lumbar spine, femoral neck, and total hip BMD responses to denosumab. CONCLUSIONS: In men with prostate cancer receiving ADT significantly higher BMD response rates were observed with denosumab vs. placebo. TRIAL REGISTRATION: This study is registered with ClinicalTrials.gov with the identifier NCT00089674.